Running vs. resistance exercise to counteract deconditioning induced by 90-day head-down bedrest - Robin, Adrien; Wang, Linjie; Custaud, Marc-Antoine; Liu, Jiexin; Yuan, Min; Li, Zhili; Lloret, Jean-Christophe; Liu, Shujuan; Dai, Xiaoqian; Zhang, Jianfeng; Lv, Ke; Li, Wenjiong; et al. (Frontiers in Physiology, 2022)
Spaceflight is associated with enhanced inactivity, resulting in muscular and cardiovascular deconditioning. Although physical exercise is commonly used as countermeasure, separate applications of running and resistive exercise modalities have never been directly compared during long-term bedrest. This study aimed to compare effectiveness of two exercise countermeasure programs, running and resistance training, applied separately, for counteracting cardiovascular deconditioning induced by 90-day head-down bedrest (HDBR). Maximal oxygen uptake (V̇O2max), orthostatic tolerance, continuous ECG and blood pressure (BP), body composition and leg circumferences were measured in control group (CON: n=8), running exercise group (RUN: n=7) and resistive exercise group (RES: n=7). After HDBR, the decrease in V̇O2max was prevented by RUN countermeasure and limited by RES countermeasure (-26% in CON p<0.05, -15% in RES p<0.05, -4% in RUN ns). Subjects demonstrated surprisingly modest orthostatic tolerance decrease for different groups, including controls. Lean mass loss was limited by RES and RUN protocols (-10% in CON vs. -5–6% in RES and RUN). Both countermeasures prevented the loss in thigh circumference (-7% in CON p<0.05, -2% in RES ns, -0.6% in RUN ns) and limited loss in calf circumference (-10% in CON vs. -7% in RES vs. -5% in RUN). Day-night variations in systolic BP were preserved during HDBR. Decrease in V̇O2max positively correlated with decrease in thigh (r=0.54, p=0.009) and calf (r=0.52, p=0.012) circumferences. During this 90-day strict HDBR, running exercise successfully preserved V̇O2max, and resistance exercise limited its decline. Both countermeasures limited loss in global lean mass and leg circumferences. The V̇O2max reduction seems to be conditioned more by muscular than by cardiovascular parameters.